Learning Tenses Using “Tepuk Keledai Cerdik” Technique for First Semester Students of English Education Program - Al Hikmah (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Tenses materials are basic grammar lessons that make students better at understanding grammar learning at the next level. The learning situation in this monotonous pandemic period is, of course, very detrimental for students if lecturers do not try to create innovations and learning creations.